PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN DAN HARGA MINUMAN KOPI DI KEDAI KOPI DUAPERTIGA, KABUPATEN SINJAI - Hamsidar, Hamsidar; Astaman, Putra; Aisyah, Megawati; Nurdin, Fadilah (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2025)
Business owners need to consider various important factors so that their businesses can survive and thrive amid increasingly intense competition. The purpose of this study is to examine these factors in the context of the local coffee shop Kedai Duapertiga in Sinjai Regency. This research was conducted at Kedai Kopi Duapertiga, located on Jln. Cengkeh, Balangnipa Village, Sinjai Regency, from February to May 2025. This research is quantitative in nature with an associative approach. Data analysis uses multiple linear regression analysis. The results show that partially, product quality and service quality have a positive and significant effect on customer satisfaction. However, price does not have a significant effect on customer satisfaction. Simultaneously, the three variables still have a significant effect on customer satisfaction. The coefficient of determination (R²) is 74.3%, indicating that the independent variables explain 74.3% of customer satisfaction, while the rest is influenced by other factors outside the study.